2017
DOI: 10.3847/1538-4357/834/1/92
|View full text |Cite
|
Sign up to set email alerts
|

Lamost Observations of Flaring M Dwarfs in the Kepler Field

Abstract: A sample of the LAMOST spectra of the early type M0-M3 dwarfs is compared with the Kepler observations. It is found that M dwarfs with strong chromospheric emission in H α have large flare activity in general.The rotational periods derived from the Kepler measurements have close correlations with the sizes of the flares, the power-law distribution index and the equivalent widths of the H α emission. A clear trend exists for higher magnetic activities being detected in faster rotating M dwarfs (rotation periods… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 20 publications
3
17
0
Order By: Relevance
“…Thus, this confirms the results of Candelaresi et al (2014) who also found that the slope for the flare energy distribution is nearly constant. This was recently confirmed with LAMOST by Chang et al (2017).…”
Section: Relation With Rotation Periodsupporting
confidence: 58%
See 1 more Smart Citation
“…Thus, this confirms the results of Candelaresi et al (2014) who also found that the slope for the flare energy distribution is nearly constant. This was recently confirmed with LAMOST by Chang et al (2017).…”
Section: Relation With Rotation Periodsupporting
confidence: 58%
“…To make the statistics of the sample more robust and disentangle binarity from the flaring nature, detailed spectroscopic studies of the flare stars are required to exclude the possibility of a companion (Karoff et al 2016;Pedersen et al 2017;Chang et al 2017). In particular, the existence of flaring Astars conflicts with our current understanding of stellar evolution, and these could use special spectroscopic scrutiny.…”
Section: Discussionmentioning
confidence: 99%
“…Data 130 Release 3 includes 5.75 million spectra and stellar parameters for >3 million stars. LAMOST has an ideal view of the field observed for four years by the Kepler satellite, and several groups have used the ∼50,000 stars observed in the Kepler field to characterize its stellar populations (e.g., Dong et al 2014;Frasca et al 2016;Ren et al 2016;Chang et al 2017;Dong et al 2017). Other work based on LAMOST spectra includes measurements of stellar activity (e.g., Fang et al 2016) and identification of important subclasses of objects from ultra-metal-poor stars (e.g., and metalliclined Am stars (e.g., Hou et al 2015).…”
Section: Overview Of the Survey Landscapementioning
confidence: 99%
“…The cooler stars such as K and M dwarfs also show similar, surprisingly energetic flares (Kowalski et al 2013). Superflares on the most active stars, M dwarfs, are common and have been widely studied (e.g., Walkowicz et al 2011;Hawley et al 2014;Chang et al 2017). During these flare events, the total energy could be more than 10 34 erg, accompanied by chromospheric and coronal emission lines.…”
Section: Introductionmentioning
confidence: 99%